INVENTARISASI DAN IDENTIFIKASI TUMBUHAN PANGAN DI KECAMATAN SABU BARAT KABUPATEN SABU RAIJUA - Heke, Mibels Novarisat Jon; Ledo, mellissa E S; Ballo, Apriliana (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
East Nusa Tenggara (NTT) is one of Indonesia's provinces rich in natural resources and plant biodiversity. The inventory of food plants involves identifying, recording, and mapping plant species used as food sources. In this context, identification refers to the process of determining plant species. West Sabu District in Sabu Raijua Regency is home to various plant species traditionally used by local communities to meet their daily food needs. Observations indicate that residents still rely heavily on traditional knowledge to utilize food plants found in their surroundings—such as in home gardens, yards, and rice fields. However, this knowledge is largely oral, raising concerns about its potential loss over time. This study, conducted from April to June in the villages of Depe, Raenalulu, Ledeana, and Raedeva (West Sabu District), employed a descriptive qualitative method. Findings revealed 29 plant species across 21 families, with Poaceae and Fabaceae being the most commonly used. The most frequently utilized plant organ was the fruit (from 16 species), while shoots were the least utilized (only 1 species). The methods of food preparation included mashing (5.17%), cooking (10.35%), and direct consumption (14.48%).